Nuchal Cystic Hygroma in Fetus: A Case Report - Kohli, Esha; Sawal, Anupama; Kohli, Gaurav (Curēus (Palo Alto, CA), 2024)
Cystic hygromas detected prenatally usually have a poor prognosis; hence, a correct and early diagnosis is essential. A prenatal ultrasound may detect a cystic hygroma as early as 10 weeks of gestation. Knowledge of the imaging findings and prognostic factors is necessary for effective perinatal counseling. Nuchal cystic hygromas (NCHs) in fetuses present a rare and challenging medical situation for prenatal care providers. This case report aims to describe a particular case of NCH detected through routine prenatal ultrasound, emphasizing the diagnostic demanding situations, management decisions, and final results. The etiology of NCHs remains multifactorial and complicated. Despite the fact that a few instances are sporadic, a great proportion has been associated with genetic aberrations, mainly chromosomal anomalies such as Turner syndrome, trisomy 21, and trisomy 18. Recent advances in molecular genetic testing, together with chromosomal microarray analysis and non-invasive prenatal testing, have facilitated the identification of the underlying genetic factors, contributing to a better knowledge of the pathogenesis of NCHs. In fetuses, they pose a complex scientific state of affairs with diverse implications. Advances in diagnostic techniques and genetic testing have notably progressed our capacity to become aware of related anomalies, offering precious insights into diagnosis and management alternatives. However, further research is warranted to get to the bottom of the underlying mechanisms of NCH development, enhance prenatal counseling, and refine therapeutic procedures to optimize outcomes for affected pregnancies.